Trade Openness, innovation, and Economic Growth: A causal Effect Analysis of OECD Countries - Shabbir, Muhammad Nadir; Liyong, Wang; Iftikhar, Kainat (Pakistan Journal of Economic Studies (PJES), 2021)
The purpose of this paper is to examine the relationship between a country's economic growth and its trade openness, innovation, and technological advancement. We discover evidence that public policies that promote increased trade openness have a significant impact on a country's level of innovation. The positive correlation between openness to trade and innovation is significantly stronger in developing countries. We dissect the causal relationship between economic growth and trade precisely by applying new advances in the econometric method for heterogeneous panel data to 127 OECD countries divided into developed and emerging economies. We examine Granger causality using a test for heterogeneous board knowledge. The findings contradict the hypothesis that trade openness and economic growth have a general, unidirectional, and even homogeneous relationship in developing countries and the OECD, but not in developed countries.